THE SIGNIFICANCE OF ANGIOGENIC BIOMARKERS AND HEMOSTATIC SYSTEM PARAMETERS IN FORECASTING PREGNANCY COMPLICATIONS FOLLOWING IVF - Nazrullaeva Oygul Muradilloevna (Modern American Journals, 2025)
The article shows that early detection of disorders in the hemostasis system by the type of genetic thrombophilia and genetically non-deterministic hypercoagulation, as well as timely diagnosis of changes in the levels of angiogenic growth factors (soluble receptor of vascular endothelial growth factor 1and placenta growth factor) in the first trimester of pregnancy allows us to identify risk factors for the development of the threat of termination of pregnancy, PI and gestosis in pregnant women after IVF
Keywords: Pregnancy, genetic thrombophilia, hypercoagulation, angiogenic growth factors